KOLABORATIF PENGELOLAAN PARIWISATA TELUK KILUAN (Collaborative Management Of The Teluk Kiluan Tourism) - Tresiana, Novita; Duadji, Noverman (Seminar Nasional FISIP Unila, 2017)
The collaborative process is a key dimension of communications-based tourism management planning. The collaborative process requires the participation of the community, the existence of equality of power and the competence of actors as a guarantee of the sustainability of the dialogue of authentic citizens. The purpose of this article describes whether the prerequisites that are owned and required for the creation of a collaborative process in the management of Teluk Kiluan tourism exist, so that collaborative processes do not produce a pseudodemocracy but benefit for the community. The method used is qualitative descriptive. The data collection of this study is done through the inventory stages of both primary and secondary data. The results of the study find that the low requirements of Teluk Kiluan indicate a non-collaborative community condition requiring changes in policy strategies through government support, community participation, direct benefits, local resource use, local institutional strengthening and synergy between levels and regions. Keywords: Collaborative, Planning and Community